Retroviral recombination during reverse transcription. - Goodrich, D W (1990)
After mixed infection, up to half of related retroviruses are recombinants. During infection, retroviral RNA genomes are first converted to complementary DNA (cDNA) and then to double-stranded DNA. Thus recombination could occur during reverse transcription, by RNA template switching, or after reverse transcription, by breakage and reunion of DNA. It has not been possible to distinguish between these two potential mechanisms of recombination because both single-stranded cDNA and double-stranded proviral DNA exist in infected cells during the eclipse period. Therefore we have analyzed for recombinant molecules among cDNA products transcribed in vitro from RNA of disrupted virions. Since recombinants from allelic parents can only be distinguished from parental genomes by point mutations, we have examined the cDNAs from virions with distinct genetic structures for recombinant-specific size and sequence markers. The parents share a common internal allele that allows homology-directed recombination, but each contains specific flanking sequences. One parent is a synthetically altered Harvey murine sarcoma virus RNA that lacks a retroviral 3' terminus but carries a Moloney murine retrovirus-derived envelope gene (env) fragment 3' of its transforming ras gene. The other parent is intact Moloney virus. Using a Harvey-specific 5' primer and a Moloney-specific 3' primer, we have found recombinant cDNAs with the polymerase chain reaction, proving directly that retroviruses can recombine during reverse transcription unassisted by cellular enzymes, probably by template switching during cDNA synthesis. The recombinants that were obtained in vitro were identical with those obtained in parallel experiments in vivo.